2007
DOI: 10.1021/ja076453m
|View full text |Cite
|
Sign up to set email alerts
|

Isomeric Forms of Heavier Main Group Hydrides:  Experimental and Theoretical Studies of the [Sn(Ar)H]2 (Ar = Terphenyl) System

Abstract: A series of symmetric divalent Sn(II) hydrides of the general form [(4-X-Ar')Sn(mu-H)]2 (4-X-Ar' = C6H2-4-X-2,6-(C6H3-2,6-iPr2)2; X = H, MeO, tBu, and SiMe3; 2, 6, 10, and 14), along with the more hindered asymmetric tin hydride (3,5-iPr2-Ar*)SnSn(H)2(3,5-iPr2-Ar*) (16) (3,5-iPr2-Ar* = 3,5-iPr2-C6H-2,6-(C6H2-2,4,6-iPr3)2), have been isolated and characterized. They were prepared either by direct reduction of the corresponding aryltin(II) chloride precursors, ArSnCl, with LiBH4 or iBu2AlH (DIBAL), or via a tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
122
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 101 publications
(137 citation statements)
references
References 57 publications
15
122
0
Order By: Relevance
“…In principle, the normal oxidation states of Sn are characterized by IS values of 0 to w2.22 for Sn(IV), 2.56 to w4.55 for Sn(II), and w2.0 to w2.56 for Sn(0), all in mm s À1 [8]. In a previous study [9] an IS of 1.370(4) was ascribed to Sn(III) in the compound 3,5 iPr 2 -Ar * SnSn(H 2 )-3,5-iPr 2 -Ar * with an Sn(I) site associated with an IS of 3.252(7) mm s À1 all at 90 K. However, the two tin sites in 2 of the present study differ very significantly from those in the Power et al compound 16 [9], including an SneFe ligation in one case and an SneCl ligation in the other, so that no meaningful comparison between the two cases can be made on the basis of presently available data.…”
Section: Oxidation State Of Snmentioning
confidence: 97%
“…In principle, the normal oxidation states of Sn are characterized by IS values of 0 to w2.22 for Sn(IV), 2.56 to w4.55 for Sn(II), and w2.0 to w2.56 for Sn(0), all in mm s À1 [8]. In a previous study [9] an IS of 1.370(4) was ascribed to Sn(III) in the compound 3,5 iPr 2 -Ar * SnSn(H 2 )-3,5-iPr 2 -Ar * with an Sn(I) site associated with an IS of 3.252(7) mm s À1 all at 90 K. However, the two tin sites in 2 of the present study differ very significantly from those in the Power et al compound 16 [9], including an SneFe ligation in one case and an SneCl ligation in the other, so that no meaningful comparison between the two cases can be made on the basis of presently available data.…”
Section: Oxidation State Of Snmentioning
confidence: 97%
“…Distanynes were also shown to add H 2 , [5] and the structure of the product is governed by the size of the ligands. [6] Very recently [GaArЈ] 2 (ArЈ = 2,6-(2,6-iPr 2 C 6 H 3 ) 2 C 6 H 3 ) was treated with H 2 at room temp. and 1 bar to give [ArЈGa(µ-H)H] 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In a more detailed investigation74 we showed that the tin hydride products could also be synthesized by reduction of aryl tin halide precursors with a variety of reducing agents. Calculations on the various hydride products showed that they had similar stability but that as the bulk of the substituents increases (, , cf.…”
Section: Reactions With Unsaturated Small Moleculesmentioning
confidence: 99%